2015
DOI: 10.1111/oik.02778
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of age‐related changes inHaemoproteusinfection in a passerine bird

Abstract: Blood parasites such as malaria and related haemosporidians commonly infect vertebrate species including birds. Understanding age-specifi c patterns of parasite infections is crucial for quantifying the fi tness consequences of parasitism for hosts and for understanding parasite transmission dynamics. We analyzed longitudinal and cross-sectional infection data in house martins Delichon urbica , a migratory bird suff ering from intense haemosporidian infection. We separated within-from among-individual eff ects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 61 publications
2
50
1
1
Order By: Relevance
“…There was a higher haemosporidian prevalence in young than in experienced birds, probably due to selective disappearance of infected birds (Marzal et al 2016). There was a higher haemosporidian prevalence in young than in experienced birds, probably due to selective disappearance of infected birds (Marzal et al 2016).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…There was a higher haemosporidian prevalence in young than in experienced birds, probably due to selective disappearance of infected birds (Marzal et al 2016). There was a higher haemosporidian prevalence in young than in experienced birds, probably due to selective disappearance of infected birds (Marzal et al 2016).…”
Section: Discussionmentioning
confidence: 89%
“…Thus we were able to assign the age of individuals accurately, assuming un-ringed birds to be yearlings at first capture that had originated from outside the study area, and assuming that disappearance of ringed breeders from the colony indicated mortality rather than dispersal (Marzal et al 2016). Adult House Martins were captured and identified with numbered metal rings.…”
Section: Field Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, lineages act as independent species (Nilsson et al 2016), show spatial heterogeneity within a local environment (Wood et al 2007), and can have different infection strategies (Nilsson et al 2016). However, before inferences can be made on the effect that each parasite lineage has on host population dynamics, we must first determine the timing of parasite transmission , Asghar et al 2011, because age-dependent parasite infections can influence the strength of selection imposed on a host population, as well as effect estimates of parasite-mediated fitness costs (Marzal et al 2016). However, before inferences can be made on the effect that each parasite lineage has on host population dynamics, we must first determine the timing of parasite transmission , Asghar et al 2011, because age-dependent parasite infections can influence the strength of selection imposed on a host population, as well as effect estimates of parasite-mediated fitness costs (Marzal et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, breeding dispersal is negligible in our study sites with less than 0.1% of breeding individuals (i.e. ≥ first year of age) among the more than 10 000 adults ringed in the study population during more than 20 yr ever being recorded at another colony in the same or subsequent years (Marzal et al ). Moreover, age at first reproduction occurred at the age of one year for the majority of individuals since all but one of more than 500 individuals marked as nestlings were recruited as first‐year breeding adults.…”
Section: Methodsmentioning
confidence: 99%